FSH receptor N680S genotype-guided gonadotropin choice increases cumulative pregnancy and live birth rates after in vitro fertilization - Hjelmér, Ida; Nilsson, Mathilda; Henic, Emir; Jędrzejczak, Piotr; Nenonen, Hannah; Ozegowska, Katarzyna; Giwercman, Aleksander; Kitlinski, Margareta Laczna; Giwercman, Yvonne Lundberg (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to compare cumulative [fresh and frozen embryo transfers from one ovarian stimulation (OS) cycle] pregnancy and live birth rates in women for whom the choice between recombinant FSH (rFSH) and urinary FSH (uFSH) for OS was linked to FSH receptor (FSHR) N680S genotype and compared these to non-genotyped controls.MethodsTo define the optimal combination of FSH type and FSHR genotype, 475 women were allocated to either the rFSH group or to the uFSH group for OS. The number of aspirated oocytes, cumulative pregnancy rates, and live birth rates in the first OS cycle were determined. Subsequently, their FSHR N680S (rs6166) variant was analyzed. Clinical data were backed up by in vitro experiments, in which COS-1 cells were transfected with homozygous FSHR variants and stimulated with either uFSH or rFSH. cAMP was measured to evaluate receptor activity. Thereafter, a sub-cohort of 221 who received optimal FSH treatment in relation to their FSHR genotype was selected from the total cohort of 475 women. Cumulative pregnancy and live birth rates were compared between 991 non-genotyped controls and these 221 women. Binary logistic regression was used to explore the odds ratios (ORs) and 95% confidence intervals (CIs) for cumulative pregnancy and live birth rates in the first OS cycle among genotyped and optimally treated women, with the non-genotyped cohort set as the reference. Adjustment was made for age, body mass index, and method of fertilization.ResultsThe combined clinical and in vitro data indicated that uFSH was the optimal choice for FSHR N680S S-allele carriers, whereas rFSH was the hormone of choice for asparagine (NN) subjects. The sub-cohort consisting of uFSH-treated S-carriers together with rFSH-treated NN-carriers had a significantly higher chance of pregnancy (51% vs. 40%; OR: 1.40, 95% CI 1.12-1.75, p=0.003) and live birth (40% vs. 29%; OR: 1.55, 95% CI 1.23-1.96, p<0.001) compared to non-genotyped women, in whom the choice of hormone was based on a standard clinical evaluation.ConclusionA significantly increased chance of pregnancy and live birth can be achieved by a genotype-guided approach. While the administration of uFSH should be the choice for S-carriers, rFSH is beneficial for NN-carrying women.